KAJIAN KOMPARASI MEDIASI PERCERAIAN PENGADILAN AGAMA INDONESIA DAN MAHKAMAH SYARIAH MALAYSIA: Comparatife Study of Divorce Mediation in Indonesian Religios Court and Malaysia Sharia Court - Indra Cahya; Asep Iwan Iriawan (AMICUS CURIAE, 2024)
The Religious Courts, one of whose powers is to resolve divorce issues for Muslim people. Before the divorce trial begins, the parties must mediate in court assisted by a mediator. Whereas in Malaysia the Religious Courts are called the Sharia Courts whose duties are to resolve issues related to Islamic matters, if a husband and wife have an agreement to file for divorce, the Sharia Court shall resolve the matter by conducting mediation or sulh first. Sulh is an attempt to reconcile couples in the context of marriage as an attempt to reconcile between husband and wife before the couple is legally divorced and separated. The problem is how are the similarities in divorce mediation between the Indonesian Religious Court and the Malaysian Sharia Court and how are the differences in divorce mediation between the Indonesian Religious Court and the Malaysian Sharia Court. This study uses a descriptive comparative normative research type using secondary data obtained from the literature. Secondary data was analyzed qualitatively by using deductive logic. Based on the results of a comparative study of divorce mediation at the Indonesian Religious Court and at the Malaysian Sharia Court, they have similarities and differences. The similarities are regarding the time of the mediation process and the appointment of mediators, while the differences are regarding the method of conducting the mediation, the requirements of the mediator, the mediation arrangements, the time limit for the mediation process, and the number of mediators.